EMBRYO CULTURE AND IN VITRO CLONAL PROPAGATION OF OAK (Quercus aegilops L.) - & Toma, Fadladeen (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
An attempt was done to develop a micropropagation protocol for oak using embryo culture. Oak is considered a hard-to-root woody plant by conventional propagation methods, that’s why using tissue culture techniques is a very suitable alternative method. For oak embryo culture, WPM was used and found to be better than MS medium for embryo germination which gave 66.13%. As well as adding of GA3 to the medium improved the germination rate of embryos (43.25% and 82.25 %). At initiation stage, WPM was used and found to be the best medium by giving the highest number of shoots/ explant which was 1.80, the highest number of leaves (15.17 leaves/ explant) and the longest shoots (1.42 cm) followed by MS medium then GD which gave the lowest parameters which gave 0.98 shoots/ explant, 7.20 leaves/ explant and 1.06 cm shoot length. At shoot multiplication stage, BA was better than Kinetin for multiplication of oak explants. The addition of BA at 3 mg.l-l gave the highest number of shoot and leaves which were 3.33 and 26.11 respectively. The longest shoots were achieved when 4.5 mg.l-l of BA was used. Furthermore, kinetin at 3 and 4.5 mg-l gave the lowest parameters which were 1 cm in length and 1.54 leaves/ explant. For rooting stage, NAA was better than IAA in giving better parameters and rooting percentage. The highest number of roots and rooting percentage were achieved when 1 mg.l-l was added by giving 6 roots/ explant and 100% rooting percentage. While the longest roots were achieved when 0.5 mg.l-l of NAA was used (3.67 cm) followed by 1.5 mg.l-l IAA which gave 3.55 roots/ explant with rooting percentage 90%. The produced plantlets were successfully acclimatized and transferred to the open-air conditions with a rate reached 85%.